Nurturing Islamic and Socio-political Thoughts in Riau and Beyond: Exploring Raja Ali Haji’s Works - Helmiati, Helmiati (Journal of Al-Tamaddun, 2021)
Raja Ali Haji is best-known as the author of the famous poem "Gurindam Dua Belas", even though he authored some other important poetries and proses that are often overlooked. In fact, he wrote a vast number of subjects in a variety of literary genres ranging from culture, history, politics, and jurisprudence to language. While other researchers such as Junus, Putten, Andaya, and Syam, have been concerned mainly with his works on culture, history, language, and jurisprudence, this study explores his works on Islamic and socio-political thoughts. Employing content analysis of relevant manuscripts and books, this study finds that Raja Ali Haji played various roles including as a religious scholar and a political thinker who synthesized culture and politics with Islam and whose thoughts have been extensively influential, mainly in Riau and beyond. This finding weakens the earlier assumption that Al-Mawardi political thoughts were more influential in the Malay world.